Effects of professional learning communities on job satisfaction of female teachers in Vietnam - Ly, Nguyen Thanh; Hong, Nguyen Van (Institute of Advanced Engineering and Science, 2025)
This study focuses on this topic to better understand how professional learning communities (PLCs) affect the work satisfaction of female primary school teachers in Vietnam. By utilizing the Statistical Package for the Social Sciences (SPSS 26) to evaluate our sample of 675 female primary school teachers, we were able to provide insight into the efficacy of PLCs in enhancing work satisfaction levels. The findings show that, among this population, participation in PLCs is significantly correlated with higher job satisfaction. In which, the collective learning and application (LA) element is followed by the shared and supportive leadership (SS), supportive conditions—relationships (SR), supportive conditions—structures (CS), and shared personal practice (PP) elements, shared values and vision (VV) has the most minor influence. Using PLCs as a workable solution to improve female educators’ working conditions and job satisfaction emphasizes the possible advantages for educational practice and policy.